MANAJEMEN DIGITALISASI SISTEM INFORMASI BARANG PERSEDIAAN BERBASIS APLIKASI (SIBAPER) SEBAGAI UPAYA MEMBERIKAN TRANSPARANSI DAN MENGEMBALIKAN KEPERCAYAAN PUBLIK PADA PENGADILAN AGAMA PALOPO - Patadungan, Hendriawan; Nurhaenih, Hj; Safrillah, Nur Fadhillah; Indarwati, Nur (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
The Palopo Religious Court faces challenges in managing inventory efficiently and transparently. This problem has an impact on public trust in these institutions. To overcome this problem, an Application-Based Inventory Information System (SIBAPER) has been developed. This research aims to evaluate the implementation of SIBAPER in increasing transparency and restoring public trust in the Palopo Religious Courts. The research methodology involves descriptive analysis of data before and after SIBAPER implementation, as well as internal and external user perception surveys. The research results show that SIBAPER has succeeded in increasing the efficiency of inventory management, reducing errors in recording, and making information easier for stakeholders. Peningkatan transparansi ini berdampak positif terhadap kepercayaan publik, yang tercermin dari peningkatan kepuasan dan kepercayaan pengguna. Dengan demikian, digitalisasi sistem informasi melalui SIBAPER terbukti efektif sebagai solusi dalam meningkatkan transparansi dan kepercayaan publik di Pengadilan Agama Palopo.